Knowledge, attitude and practice regarding COVID-19 among healthcare workers in Chitwan, Nepal - Nepal, Richa; Sapkota, Kalyan; Paudel, Pramod; Adhikari, Bhojraj; Adhikari, Kalidas; Sapkota, Kiran; Nepal, Rhishikesh; Adhikari, Bishow Nath; Paudyal, Nabin (Journal of Chitwan Medical College, 2020)
Background: The cases of Coronavirus disease-2019 (COVID-19) has been gradually increasing in Nepal. The objective of this study was to evaluate knowledge, attitude and practice regarding COVID-19 among healthcare workers in Chitwan, one of the districts located in central Nepal. Methods: It was a descriptive, cross-sectional study, conducted among healthcare workers from different health institutions of Chitwan, over the span of two weeks from 1st April, 2020 till 14th April, 2020. Bivariate analyses of knowledge, attitude and practice scores were done with different variables using appropriate tests in SPSS IBM version 25. Results: Out of 353 responses, 166 (47%) were nurses, 102 (28.9%) were doctors, 41 (11.6%) were health assistants, 7 (2%) were community medical assistants, and the remaining 37 (10.5%) were categorized as others. 290 (82.2%) healthcare workers obtained moderate to good knowledge scores, 295 (83.6%) obtained moderate to good practice scores, and 321 (90.9%) had positive attitude scores. Doctors had highest mean knowledge scores (23.70 ± 4.48, p value- 0.000) and health assistants had highest mean practice scores (15.10±3.61, p value- 0.007). Positive correlation was obtained between knowledge and practice scores (r= 0.476, p value- 0.000); and attitude and practice scores (r= 0.238, p value- 0.000). Only 20.4% healthcare workers were confident to handle the pandemic in their healthcare setup. Conclusions: The majority of healthcare workers had moderate to good knowledge and practice scores and had a positive attitude toward COVID-19. There was a significant association between knowledge, attitude and practice scores obtained by healthcare workers from Nepal.